Coating of Carbon Nanotubes Using Chemical Method to Enhance the Corrosion Protection of Copper and Aluminum Metals in Seawater Medium - Raheema, Mazin Hasan (Iraqi Journal of Science, 2023)
In this study, carbon nanotubes were prepared using a pure chemical method modified similar to the Hummers method with simple changes in the work steps. The carbon nanotubes were then coated and reduced on copper and aluminum metals using the electrodeposition method (EDP) for corrosion protection application in seawater medium (NaCl 3.5%) at four different temperatures: 20, 30, 40, and 50 °C, which were studied using three electrode potentiostats. All corrosion measurements, thermodynamics, and kinetics parameters were nominated from Tafel plots. The films deposited by the carbon nanotubes were examined by the SEM technique, and this technique showed the formation of carbon nanotubes.